STUDY ON NORMAL HRMATOLOGICAL VALUES OF ARABIAN RACE HORSES - K.Al-Delaimi‎, A.; J. Ghazi‎, A. (The Iraqi Journal of Veterinary Medicine, 1987)
Hematological values for sixty clinically normal Arabian bred race horses of both sexes were estimated.Red cell ,count, hemoglobin concentration, packed cell volume, mean corpuscular volume, mean ‘corpuscular hemoglobin concentration, white cell count, differential leukocytic count, total serum protein, albumin and globulin were determined by using several laboratory techniques. It appeared that the total serum protein and globulin were significantly higher in the stallions than those in mares (P < 0.05) whereas the results of other hemaltological parameters were comparable and the mean values did not show significant differences (P > 0.05).